Non-Jurisdictional Conventionality Control in the Recomendations of the National Human Rights Commission: An Upward Trend - González Rincón, Ana Cristina (2025)
The model of conventionality created by the Inter-American Court can be used by other bodies dedicated to the protection of human rights, such as the National Human Rights Commission in Mexico, in addition to judges and courts. However, its participation through non-jurisdictional conventionality control continues to be questioned because of the improper powers of the judicial system. The objective of this article is to demonstrate through examples and cases that there is a tendency in the recommendations of the CNDH to carry out this control under the parameters established and outlined by the Inter-American Court. In particular, four different ways in which the control of conventionality is manifested are analyzed, and reasons are given in favor of continuing to expand this doctrine in a uniform manner, in order to strengthen the protection of human rights and to consolidate the articulation that exists between national and international law.